The Australian Picture - Luntz, Harold (Victoria University of Wellington Law Review, 2004)
Australia faces a climate of change with accident compensation following recent high profile personal injury cases, the collapse of two major health insurers, and the release of the Ipp Committee Report. This paper follows Australia's response to these developments, focusing on New South Wales' initial reform of tort law, and suggests that the current and proposed changes may cause more harm to an already fragile system.